4D seismic analysis: discriminating between saturation and pressure changes form a data acquired Offshore Equatorial Guinea - Msolo, Andile Lucky (Department of Geological Sciences, 2017)
4D seismic analysis is used to understand the performance of a producing oil field in order to increase production and mitigate risk. This is done by interpreting changes in water saturation and changes in effective pressure in the reservoir, which allows production to be maximized safely. In this project, I determined saturation and pressure changes in an oil field offshore Equatorial Guinea. I used Landrø's technique as a basis for the analysis, however Landrø's technique requires the presence of reservoir samples. For this project, rock samples of the reservoir were not available; this led me to modify Landrø's methodology using approximations based on well-accepted rock physics relationships. I tested this new methodology on a synthetic model, which gave encouraging results, after which it was applied to real seismic data. Pressure and saturation changes estimated in the reservoir indicate that the northern part of the reservoir experienced a decrease in pore pressure. The saturation changes over the northern part of the reservoir are not prominent. The central and southern parts of the reservoir show an increase in water saturation accompanied by an increase in pore pressure. The results are consistent with the production and injection history of this area. A comparison between saturation before production, saturation changes after production and pressure changes after production indicates an area (on the northern part of the reservoir) which shows fluid anomalies before production and does not show any production (or 4D) effects. New production wells could potentially be drilled in this area to increase production.